SISTEM TERINTEGRASI UNTUK TOKO PERACANGAN di Toko Kita dan Warung Pojok (Wapo) Malang - Andarwawti, Mardiana (MATICS, 2015)
Abstractâ€”Mother-housewife is now pretty much do a sideline in order to assist in meeting the economic needs of the family, in addition to fulfilling its obligation to take care of the household. One of them with a business carried retail shop at home or near home to sell groceries and other household purposes. Currently the constraints are reduction in turnover of goods that is not maximized, because many competitors of similar business and reach customers only residential environment,Â  a lot of goods in warehouses and on display is lost, and are not know for sure and written for most items sold in the market.Solutions offered to help improve the circulation of goods made to maximize inventory system that records the entry and exit of goods and cash flow reporting system in order to determine the most goods sold and can find out the benefits for each month or each year. As for the campaign to reach out not only around the housing but also outside its territory by using SMS Gateway .The expected outcome of this program is the partner can set the system inventory information, analyze sales reports for most items sold in the market, and could use a particular computer application program control supplies. Besides, by using the SMS gateway can be used as a medium for marketing of goods for the purpose that increasingly wide range of market share not only a residential area or neighborhoodKeywords : retail shop, inventory, SMS Gateway